Validated chiral liquid chromatographic method for the enantiomeric separation of Tenofovir Disoproxil drug substance and its dosage forms - VIVEK TUMMALA; PROF. K. BASAVAIAH; DR. B.M. RAO (International Journal of Pharma and Bio Sciences, 2019)
A selective isocratic liquid chromatographic method was developed for the chiral purity of Tenofovir Disoproxil and its S-enantiomer. Superior resolution between Tenofovir Disoproxil and its enantiomer was achieved on Chiralpak ADH, (25 mm × 4.6 mm, 5 μm) column using methanol: acetonitrile (90:10, v/v) containing 2 mL of dimethyl amine as a mobile phase at 30 °C column oven temperature. The USP resolution between the enantiomers was found more than five. Mobile phase flow was fixed at a rate of 1.0 mL/min and elution was monitored at 260 nm. Limit of detection and quantitative of S-enantiomer is 0.01 μg/mL and 0.3 μg/mL respectively. The method was validated for accuracy, precision, specificity, linearity, and sensitivity. Linearity was established for Tenofovir enantiomer frm 0.2µg/ml to – 2.44 µg/mL (R2>0.95), the limit of detection (LOD) and limit of quantitation (LOQ) was found to be 0.01 µg/ml and 0.03 µg/ml respectively for Tenofovir. %RSD below 5% was observed for precision and intermediate precision and recovery results were satisfactory.